Experimental study on deformation and fracture of resistance-spot-welded (RSW) overlapping plates impacted at RSW joint by round-nosed bullet. (October 2020) - Ma, Bohan; Fan, Chunlei; Chen, Danian; Wang, Huanran; Ma, Dongfang; Zhou, Fenghua
Highlights: The ballistic tests of RSW specimens are performed on gas gun system with VISAR. The shearing near notch tip and partial opening of RSW specimens are found. The through-thickness fracture and interfacial fracture of RSW specimens are revealed. The crack propagation of corona bond and pre-crack of RSW specimens is investigated. Abstract: The ballistic tests of Q&P980 resistance-spot-welded (RSW) overlapping plates impacted at RSW joint by round-nosed bullet were performed using a single-stage gas gun system with a laser velocity interferometer system for any reflector (VISAR). The deformation and fracture mechanism of the RSW specimens were investigated by using the VISAR measured results, the metallographic cross-section observation and the scanning electron microscope (SEM) analysis of the recovered RSW specimens. The dynamic response of the RSW specimens was related to the reflection and refraction of the impact stress waves on the material interfaces and the free surfaces in the RSW specimens. The bulging, dishing, shearing near the notch tip and partial opening of the RSW specimens were discussed. With the range of loading speed and the joint configuration (overlap structure, nugget size, etc.) studied in this work, the plugging fracture should be a prevailing mode. The crack propagation of the corona bond and pre-crack of the RSW specimens under impact loading was found to affect the dynamic fracture process of the RSW specimens under bullet impact.